Aerodynamic performance of magnus wind turbine with turbine supportive structure - Magaidi, Amer M. (2019)
After going through a detailed literature review, it is perceived that the Magnus wind Turbine (MWT) can be a viable option for off grid energy conversion in certain cases of confined space and low wind speed region, where the counterpart of MWT cannot operate efficiently, However, the existing design is yet a matter of research to make it more useful in particular situation. In view of this, the main aim of present study is to improve the aerodynamic performance of MWT through adding a support structure for reduce the impact of free end status of the rotary cylinders on their aerodynamic characterises, where free end status of the cylinders depletes consumed power that uses to spin the cylinders through its impact in reduce the actual rate of cylinders rotation, and hence their tip speed ratio whose low value causes a poor performance of rotary cylinders. To overcome the above undesirable condition, this study suggests modifying magnus rotor through surrounding magnus wheel with an outer ring supported in an analogously order by supporting arms. Currently many research studies have concentrated on improving the aerodynamic performance of wind turbine through numerical, analytical and experimental studies. Computational Fluid Dynamics (CFD) offers inexpensive tool to aerodynamic blade analysis problem. Furthermore, Blade Element Moment (BEM) represents the most simplified common way to predict the overall performance of wind turbines. On the other hand, experimental studies represent the quickly assess of the computed predictive results. 2D Ansys Fluent 17.0 as a code of CFD was selected to analysis the fluid flow around the aerodynamic surfaces of the new rotor in order to predict the effectiveness of new design in improving the aerodynamic performance of MWT, where 2D simulation can provide a good result features of the fluid flow with lesser computational cost. Thereafter, BEM was directed to predict the overall performance of new designed in terms of cut-in speed and generated torque. On the other hand, experimental tests were chosen to perform on a real model of new MWT. Computed results have expected of an increase in lift force by up to 14 % which demonstrated the effectiveness of new design to improve the performance. Besides that, Analytic results of new MWT was indicated firstly to that, the cut-in velocity decreases as the λ2 increases in the specified range of λ2 ≤ 2.8. Also, the generated torque increases in effect of increasing both of wind speed and rotating rate of cylinders at delimited rang of 7.7 m/s and 2520RPM respectively. On other hand, experimental tests demonstrated the effect of tip speed ratio of cylinders (λ2) on the effectiveness and variation of produced torque. Finally, the obtained results have also achieved the performance of CP = 0.47 at λ1 of 0.17, as well as disappearance of exhibiting the spinning motion of the cylinders in bell shape.